Malignant Tumors Misdiagnosed as Liver Hemangiomas - Yıldırım, Murat Baki; Şahiner, İbrahim Tayfun and Poyanlı, Arzu and Acunaş, Bülent and Güllüoǧlu, Mine and İbiş, Cem and Tekant, Yaman and Özden, İlgin (Frontiers in Surgery, 2021)
Background and Aim: To derive lessons from the data of patients who were followed for various periods with the misdiagnosis of liver hemangioma and eventually found to have a malignancy. Material and Methods: The records of 23 patients treated between 2003 and 2018 were analyzed retrospectively. Results: Twelve patients were men and 11 were women; median (range) age was 55 (35–80). The principal diagnostic modality for the initial diagnosis was ultrasonography (n:8), magnetic resonance imaging (MRI) (n:13), and computed tomography (CT) (n:2). At our institution, MRI was performed in 16 patients; the diagnosis was made with the available MRI and CT studies in five and two patients, respectively. In other words, the ultrasonography interpretations were not confirmed on MRI; in others, the MRI or CT examinations were of low quality or they had not been interpreted properly. Fifteen patients underwent surgery; the other patients received chemotherapy (n:6) or chemoembolization (n:2). The misdiagnosis caused a median (range) 10 (0–96) months delay in treatment. The final diagnoses were hepatocellular carcinoma in 12 patients, cholangiocarcinoma in four patients, metastatic mesenchymal tumor, metastasis of colon cancer, metastatic neuroendocrine carcinoma, sarcomatoid hepatocellular carcinoma, angiosarcoma, thoracic wall tumor, and metastatic tumor of unknown primary in one patient each. Conclusions: High-quality MRI with proper interpretation and judicious follow up are vital for the accurate differential diagnosis of liver lesions.